First Report of Aeromonas schubertii Infection in Striped Snakehead Channa striata (Bloch, 1793) Fingerlings in Malaysia - Tahir, Nur Diyana Mohamad; Matori, Mohd Fuad; Gan, Han Ming (Universitas Airlangga, 2024)
Striped snakehead fingerlings Channa striata reared in a concrete pond with size 13.5 m3 (3 m ´ 3 m ´ 1.5 m) in a hatchery farm, in Labu, Negeri Sembilan, Malaysia had more than 70% mortality. The pond contained 1500 fingerlings of 5–7 cm in total length (TL). The purpose of this study was to investigate the high mortality event on the farm as part of a veterinary diagnostics service. Clinical signs observed were skin discoloration, lethargy, and anorexia. Necropsy was performed in 10 fish with gross lesions of 1–2 mm and multiple whitish nodules in the abdominal organs and most notably in the liver, and kidney. Following necropsy, bacteriology samples from the kidney and liver were inoculated onto Tryptic Soy Agar (TSA) and Blood Agar (BA). Pure colonies were observed and were Gram-negative with short rod morphology. The full-length 16S rRNA gene was amplified from the pure colonies followed by sequencing using the Nanopore MinIONâ„¢ (Oxford Nanopore, UK). The isolated strain was identified as Aeromonas schubertii based on the assembled 16S rRNA sequence showing nucleotide identity of 99.73% (top hit) to A. schubertii (GenBank Accession: NR_037014.2) while only a nucleotide identity of 97.55% was observed against Aeromonas hydrophila (GenBank Accession: NR_119190.1-), respectively. Histopathological examination from the liver, kidney, spleen, and intestine revealed granulomatous nephritis, and degeneration of tubular epithelium, with granulomatous hepatitis, splenitis, and enteritis. The prognosis of this case was grave. No treatment was given as the owner had decided to dispose of all current stock. This is the first A. schubertii infection in C. striata described in Malaysia. The findings of the present study may serve as a reference for similar cases in C. striata in the future so rapid diagnosis and treatment can be made if required.